2020
DOI: 10.1111/bor.12479
|View full text |Cite
|
Sign up to set email alerts
|

A new map of glacigenic features and glacial landsystems in central mainland Nunavut, Canada

Abstract: A new digital map of glacial geomorphic features and interpreted glacial landsystems was produced for an area covering ~415 000 km2 in the Keewatin Sector of the Laurentide Ice Sheet (LIS) in Nunavut. The map integrates information from previous surficial geology maps and >14 000 field stations, and is significantly improved by the detailed inventory of ~152 000 glacigenic features using high‐resolution ArcticDEM data and Landsat 8 imagery. From this, we identify and map coherent patterns of landform developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 124 publications
0
16
0
Order By: Relevance
“…The location of the MIS 3 shells in streamlined calcareous till on a J o u r n a l P r e -p r o o f plateau above the local (Holocene) marine limit (Fig. 5) coincides with a relatively old terrain that has largely escaped the deglacial ice flows into Repulse Bay (McMartin et al, 2021), whereas the Holocene shells collected in the same setting but below the marine limit are compatible with regional radiocarbon ages indicating a minimum deglaciation age of 8 ka. This grouping, together with the careful pretreatments used here, suggest relatively minor postdepositional alterations to the ages and support a marine episode prior to LGM in northwestern Hudson Bay.…”
Section: Laurentide Ice Sheetmentioning
confidence: 90%
“…The location of the MIS 3 shells in streamlined calcareous till on a J o u r n a l P r e -p r o o f plateau above the local (Holocene) marine limit (Fig. 5) coincides with a relatively old terrain that has largely escaped the deglacial ice flows into Repulse Bay (McMartin et al, 2021), whereas the Holocene shells collected in the same setting but below the marine limit are compatible with regional radiocarbon ages indicating a minimum deglaciation age of 8 ka. This grouping, together with the careful pretreatments used here, suggest relatively minor postdepositional alterations to the ages and support a marine episode prior to LGM in northwestern Hudson Bay.…”
Section: Laurentide Ice Sheetmentioning
confidence: 90%
“…During ice sheet retreat there were marine incursions in eastern (Tyrrell Sea; Shilts et al 1987), and northern Keewatin (Prest et al, 1968;Dyke, 2004). There is widespread evidence of subglacial meltwater activity including eskers and meltwater corridors radiating out from the migrating ice divide, directly beneath which they are rare (Shilts et al, 1987;Aylsworth and Shilts, 1989;Storrar et al, 2013Storrar et al, , 2014bLewington et al, 2020;McMartin et al, 2020). Esker formation here has been linked to increased surface meltwater associated with rapid melting of the LIS towards the end of deglaciation (Storrar et al, 2014a).…”
Section: Regional Settingsmentioning
confidence: 99%
“…The small-scale periglacial features (mudboils, solifluction lobes, and ice-wedge troughs), glacial landforms (morainic ridges and shorelines), and nuances in the surficial sediments that are evident in the RPA orthomosaic are not readily apparent on the air photos that were used to compile the geological map. Similarly, new high-resolution geomorphological mapping in the same area using the 2 m resolution ArcticDEM (McMartin et al 2021) did not permit the level of detail observed with the RPA.…”
Section: Landform Mapping and Interpretationmentioning
confidence: 95%